ANALISIS SISTEM KEBIJAKAN OBJEK VITAL, PENGAMANAN FILE, DAN CYBER SECURITY PADA PT. BPJS KETENAGAKERJAAN - Edy Soesanto; Leonaldi Hutajulu; Sephia Supriydi; M. Rijal (Cross-border, 2023)
Security is an important aspect in maintaining operational continuity and protecting company assets. PT. BPJS Ketenagakerjaan as a company with vital objects and sensitive data, needs to implement strong security policies and practices. This study aims to analyze the vital object security policy system, data security, and cyber security at PT. BPJS of Employment. The research method used is qualitative research. The discussion of the research is that: 1) PT. Employment BPJS has vital object security, 2) PT. Employment BPJS has file security, and 3) PT. BPJS Employment has cyber security.